Antecedents of Saving Interest at Bank Jatim Indonesia: Bank Atmosphere, Location, and Work Professionalism - Yuan Erma Septi Apsari Santoso; Joko Suyono; Damarsari Ratnasahara Elisabeth; Abdul Thalib Bin Bonn (LPPM of NAROTAMA UNIVERSITY, 2021)
The customers interest in saving is very important for bank providing banking services in the form of savings. In relation to the interest in saving, bank should conside bank atmosphere, location and work professionalism, so that the customer has a high interest in the bank. The purpose of this study is to analyze the influence of bank atmosphere, location and work professionalism on interest in saving at bank. The population in this study was Bank Jatim Indonesia, Branch of Haji Hospital Surabaya, totally of 1,908 customers, the number of samples using the Slovin formula was 95. The data analysis technique used was multiple regression analysis. The research results are: 1) There is an influence of the bank atmosphere on the interest in saving at Bank Jatim Cash Office of Haji Hospital Surabaya, 2) There is an influence of location on the interest in saving at Bank Jatim Cash Office of Haji Hospital Surabaya, 3) There is an influence of work professionalism on the interest in saving at Bank Jatim Cash Office of Haji Hospital Surabaya, 5) variable location has a dominant influence on the interest in saving at Bank Jatim Cash Office of Haji Hospital Surabaya.